3D surface analysis of coral microatolls - Gautam, Rohan (Nanyang Technological University, 2022)
Microatolls are coral colonies with living outer margins but flat, dead upper surfaces. Coral microatolls are also valuable paleo-sea-level indicators owing to both their vertical precision and the fact that they can grow and respond to sea level changes for decades to centuries, unlike other short-lived organisms. In addition, they also can be used to track tectonic changes associated with their area of growth.